The Pink Panther - Levy, Shawn; Emily Mortimer; Jean Reno; Kevin Kline; Steve Martin (USA Metro-Goldwyn-Mayer (MGM), 2006)
When the coach of the France soccer team is killed by a poisoned dart in the stadium in the end of a game, and his expensive and huge ring with the diamond Pink Panther disappears, the ambitious Chief Insp. Dreyfus (Kevin Kline) assigns the worst police inspector Jacques Clouseau (Steve Martin) to the case. His intention is to give a diversion to the press, while he uses his best men to chase the killer and thief. He assigns Gendarme Gilbert Ponton (Jean Reno) to work with Closeau and inform each step of the investigation. When Clouseau is nominated with honor to the highest prize in France, Dreyfus decides to humiliate Clouseau and take him out of the case. However Clouseau has already solved the mystery.
Loosely based on the 1964 Peter Sellers original film, where the detective must solve the murder of a famous soccer coach and find out who stole the infamous Pink Panther diamond.
Len Blum
Languages : English, Turkish Subtitles : English, Turkish, German, French, Spanish, Italian
Keywords: Mystery; Comedy